Analysis of green practice at food and beverage department of ML hotel - Kanca, I Nyoman (Journal of Commerce, Management, and Tourism Studies, 2024)
The aim of this research is to find out how far green practice behavior has been implemented in the food and beverage department at the M Hotel, Bali. Green practices are important to practice because this is one way to support efforts to reduce global warming. Green practice includes green action, green food, and green donation. Green action is demonstrated by activities that protect and preserve nature, such as reducing the use of plastic and recycling waste, and using environmentally friendly equipment. Green food consists of using local and organic food ingredients that support the environment for the long term. Meanwhile, green donations take the form of donating funds, participating in community projects, and educating the public about the impacts of environmental damage and how to overcome them. This research data collection method was carried out using interviews, observation, documentation, and literature study. Interviews were conducted with 4 people as informants. They are a manager of food and beverage, supervisor of food and beverage service, bar supervisor, and chef de partie. This research uses qualitative analysis techniques. The data is then reduced by summarizing and grouping the data and then displaying it in a table for further conclusions. In this research, it is known that the food and beverage department has implemented green practices but still need to be improved.